Analysis of irrigated and rainfed rice production in Mexico, 1980-2022 - Guzmán-Soria, Eugenio (2025)
Introduction. From 2016 to 2022, both the planted area and rice production in Mexico registered decreasing growth rates, leading to an increase in rice imports to satisfy the excess demand. Objective. To econometrically analyze the factors affecting rice production in Mexico by technology type, distinguishing between irrigated and rainfed systems. Materials and methods. A dynamic simultaneous equation model was formulated, comprising two supply equations, three price transmission models and one identity; with annual data from 1980 to 2022 on rice production in Mexico (differentiated by technology type), as well as the prices of competitive products, tradable inputs and climatic variables that determine them. To estimate the model, the Two-Stage Least Squares (2SLS) method was used and its statistical congruence was determined by means of the global significance of each equation through the F-test, its level of autocorrelation via the Durbin-Watson statistic, the individual significance of each coefficient through the Student’s t-test, and the normality of the variables with the Shapiro-Wilk test. Results. The own-price elasticities of supply for irrigated and rainfed rice were 0.6995 and 0.3871, respectively. The prices of competitive goods, particularly corn (-0.9896 and -1.2284) and wheat (-0.5279 and -0.9529), had the greatest impact on both types of supply. Conclusion. The rice supply, both irrigated and rainfed, responds positively to changes in producer prices, water availability for irrigation, and the annual average rainfall recorded in the country. Conversely, it responds negatively to changes in producer prices of competitive goods such as beans, corn, wheat, lentils and chickpeas, as well as to change in inputs such as the price of pesticides and fertilizers.